Pengaruh Perbedaan Metode Ekstraksi Terhadap Aktivitas Antibakteri (Pseudomonas aeruginosa) pada Daun Teh Hijau (Camellia sinensis L.) - Baiq Rani Salsabiella; Lina Permatasari; Neneng Rachmalia Izzatul Mukhlishah; Metta Octora (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2026)
Pseudomonas aeruginosa is an opportunistic gram-negative bacterium and is often the most common cause in people with immunocompromised problems. Infections by this bacterium, especially in patients with impaired immunity, are difficult to treat due to a number of antibiotic resistance mechanisms. The polyphenol compound Epigallocatechin Gallate (EGCG) contained in Camellia sinensis L. is known to have antibacterial activity against several bacteria so that it has the potential as an antibiotic to overcome the problem of antibiotic resistance in Pseudomonas aeruginosa. To obtain this compound, extraction with the right method is needed. In addition, the EGCG was dominant extracted at the ethyl acetate fraction. This study aims to analyze the effect of extraction methods on EGCG content and antibacterial activity (Pseudomonas aeruginosa) of ethyl acetate fractions of green tea leaves (EAFGL). The research design is an experimental laboratory using a true experimental posttest only control group design. Green tea leaf powder was extracted with 96% ethanol using the sonication and maceration methods, then fractionated evenly with n-hexane, chloroform and ethyl acetate solvents. The EGCG content of EAFGL was determined using High Performance Liquid Chromatography (HPLC). Antibacterial activity of EAFGL at the concentration 12.5; 50; 100; and 200 mg/mL were carried out using the disc diffusion method. Positive and negative control groups used Aztreonam and 10% DMSO, respectively. The antibacterial activity of EAFGL was analyzed using the Kruskal-Wallis and Mann-Whitney test. The results showed that EAFGL extracted using maceration revealed significantly higher EGCG content (170,97 ±17,51 µg EGCG/mg fraction). The EAFGL at a concentration of 200 mg/mL, obtained through maceration, exhibited the significantly (p<0.05) highest antibacterial activity against P. aeruginosa with the inhibition zone of 16.7 mm. Therefore, maceration is an appropriate method for extracting green tea leaves, as it can produce optimal EGCG content and antibacterial activity.